2010
DOI: 10.1002/cmdc.201000259
|View full text |Cite
|
Sign up to set email alerts
|

Developments in Nonsteroidal Antiandrogens Targeting the Androgen Receptor

Abstract: Addition of catalytic amounts of a phosphite‐based gold(I) catalyst efficiently triggers the intermolecular [2+2] cycloaddition of allenes and alkenes substituted by electron‐donor groups. The reaction is fast and furnishes cyclobutane derivatives in a stereoselective manner using low catalyst loadings. Besides, the same catalyst selectively affords homodimerization products from the starting allene, a process that may be conveniently fine tuned by addition of norbornene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…There are two kinds of androgen receptor antagonists, steroidal and non-steroidal chemicals 4,16 . Steroidal antiandrogens have limited clinical application due to the undesired side effects, which led to the development of nonsteroidal antiandrogens.…”
Section: Introductionmentioning
confidence: 99%
“…There are two kinds of androgen receptor antagonists, steroidal and non-steroidal chemicals 4,16 . Steroidal antiandrogens have limited clinical application due to the undesired side effects, which led to the development of nonsteroidal antiandrogens.…”
Section: Introductionmentioning
confidence: 99%
“…AR is located in the cytoplasm without the presence of a ligand and binds to heat‐shock proteins (HSPs). Once the LBD of AR binds DHT, the AR is dissociated from the HSPs, with a conformational change generating a hydrophobic groove, namely, AF2, on the surface and translocating it to the nucleus as a homodimer (Fig. ).…”
Section: The Structure and Signaling Pathway Of The Androgen Receptormentioning
confidence: 99%
“…The ligand‐activated AR binds to the specific androgen response elements in the DNA and interacts with coactivators through AF2. The interaction of coactivators with AF2 triggers the recruitment of RNA polymerase II and other transcriptional factors to form the transcription machinery for the target genes (TM) that are involved in the regulation of the proliferation and survival of prostate cells .…”
Section: The Structure and Signaling Pathway Of The Androgen Receptormentioning
confidence: 99%
“…The previous studies have been reported to target AR in either direct or indirect manner. For instance, these studies included AR antagonists for decreasing AR target gene expression , cytochrome inhibitors for blocking androgen synthesis , and Hsp90 inhibitors for degrading AR protein . Moreover, AR was crucial for the proliferation, survival, and metabolic processes in PCa cells .…”
Section: Introductionmentioning
confidence: 99%